Optimization of the Cryogenic Light-Emitting Diodes for High-Performance Broadband Terahertz Upconversion Imaging - Bai, Peng; Zhang, Yueheng; Shen, Wenzhong; Yang, Ning; Chu, Weidong (Frontiers in Physics, 2021)
High-performance terahertz (THz) imaging devices have drawn wide attention due to their significant application in a variety of application fields. Recently, the upconversion device based on the integrated homo-junction interfacial workfunction internal photoemission detector and light-emitting diode (HIWIP-LED) has emerged as a promising candidate for broadband THz upconversion pixelless imaging device. In this paper, systematical investigations on the cryogenic-temperature performances of the LED part in HIWIP-LED devices, including electroluminescence (EL) spectra and the EL efficiency, have been carried out by elaborating the radiative recombination mechanism in the quantum well, internal quantum efficiency, and the light extraction efficiency (LEE) both experimentally and theoretically. On this basis, we have further studied the operation mode of the HIWIP-LED and concluded that the LEE could directly determine the upconversion efficiency. A numerical simulation has been performed to optimize the LEE. Numerical results show that the device with a micro-lens geometry structure could significantly improve the LEE of the LED thereby increasing the upconversion efficiency. An optimal upconversion efficiency value of 0.12 W/W and a minimum noise equivalent power (NEP) of 14 pW/Hz1/2 are achieved using the micro-lens structure together with anti-reflection coating. This work gives a precise description of cryogenic LED performance in the HIWIP-LED device and provides an optimization method for the broadband HIWIP-LED THz upconversion pixelless imaging device.